Book Review: Study Of Useful Properties Of Some Coordination Compounds Containing Oximic Ligands by E. COROPCEANU, A. CILOCI, A. ȘTEFÎRȚĂ, I. BULHAC - Boris Nedbaliuc (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The monograph STUDY OF USEFUL PROPERTIES OF SOME COORDINATION COMPOUNDS CONTAINING OXIMIC LIGANDS is a synthesis of the works of the Coordination Chemistry, Enzymology and Plant nutrition and water regime laboratories during the last two decades. The monograph consists of four chapters, accompanied by bibliographic sources.